Sympathetic tone dictates the impact of lipolysis on FABP4 secretion - Kacey J. Prentice; Alexandra Lee; Paulina Cedillo; Karen E. Inouye; Meric Erikci Ertunc; Jillian K. Riveros; Grace Yankun Lee; Gökhan S. Hotamisligil (Journal of Lipid Research, 2023)
Levels of circulating fatty acid binding protein 4 (FABP4) protein are strongly associated with obesity and metabolic disease in both mice and humans, and secretion is stimulated by β-adrenergic stimulation both in vivo and in vitro. Previously, lipolysis-induced FABP4 secretion was found to be significantly reduced upon pharmacological inhibition of adipose triglyceride lipase (ATGL) and was absent from adipose tissue explants from mice specifically lacking ATGL in their adipocytes (ATGLAdpKO). Here, we find that upon activation of β-adrenergic receptors in vivo, ATGLAdpKO mice unexpectedly exhibited significantly higher levels of circulating FABP4 as compared with ATGLfl/fl controls, despite no corresponding induction of lipolysis. We generated an additional model with adipocyte-specific deletion of both FABP4 and ATGL (ATGL/FABP4AdpKO) to evaluate the cellular source of this circulating FABP4. In these animals, there was no evidence of lipolysis-induced FABP4 secretion, indicating that the source of elevated FABP4 levels in ATGLAdpKO mice was indeed from the adipocytes. ATGLAdpKO mice exhibited significantly elevated corticosterone levels, which positively correlated with plasma FABP4 levels. Pharmacological inhibition of sympathetic signaling during lipolysis using hexamethonium or housing mice at thermoneutrality to chronically reduce sympathetic tone significantly reduced FABP4 secretion in ATGLAdpKO mice compared with controls. Therefore, activity of a key enzymatic step of lipolysis mediated by ATGL, per se, is not required for in vivo stimulation of FABP4 secretion from adipocytes, which can be induced through sympathetic signaling.